Short Chain Peptide in the Treatment of Chronic Diarrhoea with Protein Maldigestion/Malabsorption - Suharyono, Suharyono (Paediatrica Indonesiana, 1990)
A trial using formula Pepti Junior (Nutricia, Holland) containing short chain peptides (SCP) was done for treating 35 children suffering from chronic diarrhoea with protein inaldigestion/malabsorption. The other 30 children who suffered from those diseases were treated with non-SCP formula, as a control. Tryptic activity test of duodenal juice was performed 2 or 3 times with a 4-week-interval. The results indicated that the gaining of body weight and improvement of protein maldigestion was better in SCP group compared with non-SCP group (p <0.01). However, the acceptance of non-SCP f ormu/a was better than SCP f ormu/a (p < 0.05); this might be due to higher tasteless MCT content in the SCP formula. No significant difference was found in duration of diarrhea during the period of treatment between the 2 groups. The explanation of these findings is that the intestinal mucosa can absorb protein better in the form of di- or tripeptide than that of free amino acids, even when the mucosal integrity was impaired due to chronic diarrhoea. It can be concluded that SCP is beneficial for treating protein maldigestion/malabsorption in chronic diarrhoeal children.